Density Functional Theory Investigation On The Electronic Structures, Dynamics, And Hyperfine Interactions Of Muoniated Tetraphenyl Derivatives - Toh, Pek Lan (2013)
Density Functional Theory investigation was performed to study the addition of muonium (Mu) in tetraphenyl derivatives, XPh4 where X = C, Si, and Ge. Based on earlier Muon Spin Rotation/ Resonance experimental results, three Mu trapping sites were considered, namely ortho, meta, and para positions on one of the phenyl rings. The stable location of Mu at the three distinct sites of the phenyl ring was determined by performing geometry optimization procedure utilizing a single XPh4 molecule with an attached Mu. The optimized geometries were then used to evaluate the energy of the system, as well as the hyperfine interactions for Mu. In addition, the mechanism for the faster dynamics of the XPh4–Mu was also studied. The effects of intermolecular interactions on the energy and hyperfine interactions for Mu at the three distinct sites were also determined. The results showed that there exists a local minimum in the energy profile at all three positions. Furthermore, the energy minimum values corresponding to Mu at the three studied sites are very similar to one another. Vibrational averaging method was utilised to determine the hyperfine coupling constants for the Mu is from the isotropic component. In order to study the rotational barrier of the XPh4–Mu, the phenyl ring with the Mu attached to it was rotated about the X–C2 bond at intervals of 10°. For all three sites, each energy profile exhibits two barriers.